Implementasi Sistem Perhitungan Cost Management Kontruksi Proyek Menggunakan Metode Earn Value Management (EVM) Berbasis Web - Ndaru Ruseno (Jurnal ICT: Information Communication & Technology, 2021)
Optimization of the Cost Management Calculation System for Project Construction Using the Earn Value Management (EVM) method has the aim of facilitating the calculation and control of costs from project construction and seeing data trends to optimize operational costs and growth strategies in the company. The EVM method itself is the most ideal method because this method can integrate time and cost so that you can find out the progress of a project faster or slower than the project schedule that should be and to find out if it is bigger or smaller than the budget it should be. EVM adds the steps that must be included in the management process, namely in the control process, and related processes for the purpose of calculating, analyzing, forecasting, reporting costs and schedule performance for evaluation and project stakeholder actions. This research produces a system that is able to optimize which is realized as a decision support in optimizing and managing or controlling a project in the company. This application is designed with the PHP programming language and uses MySQL as the database